Migrant Labor in the Arabian Gulf: A Case Study of Dubai, UAE - Sara Hamza (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
This research explores the topic of labor migration in Gulf Cooperation Council (GCC) states – Bahrain, Oman, Kuwait, Qatar, Saudi Arabia, and the United Arab Emirates – and seeks to determine how the subjugation of migrant laborers is initiated and perpetuated. The kafala (sponsorship) system has played a central role in the rapid economic development in the GCC states. Though it has allowed the Gulf States to obtain the resources necessary to develop both economically and cosmetically, the system has had an array of undesirable byproducts that have significantly altered the texture of Gulf societies. The kafalasystem promotes the rapid influx of migrants to meet the labor demand while simultaneously subjugating this imported population through its lax regulations and exclusion from the legal framework in Gulf States. As a result, the Gulf has witnessed an emergence of multi-tiered societies where locals are situated in the top tier and migrant populations consistently occupy the lowest rungs of society. The kafala system has produced structural inequalities in Gulf States and has resulted in grave human rights abuses against migrant laborers. Today, the effects of the kafala system are visible in every aspect of Gulf society. A case study of Dubai, United Arab Emirates is used to examine how legal norms produce and interact with the lived experiences of South Asian migrant laborers. The case study discusses how the kafala system unfolds in one of the most iconic cities in the world and seeks to articulate the lived experiences that are often omitted from modernization narratives.